Creative Content Strategy of Streaming Movie on SVOD by Thailand Content Providers - Korakotchamas, Passawan (Journal of Posthumanism, 2025)
The phenomenon of Video Streaming in Thailand in 2015 created online-movie providers or Video on-demand providers through Streaming with legal copyrights no less than ten providers, including a lot of the providers who infringed the copyrights. It was consistent with the consumers’ behaviors in the present time who needed convenience in hands and could not tolerate with any long waiting for anything anymore. With watching movies through Video Streaming, the viewers could be able to watch the movies through electronic gadgets connecting to the Internet conveniently, easily, and promptly. (NBTC, 2020) Nowadays, in Thailand the online-movie providers or Streaming were increasing, and the competition marketing in Thailand was seriously taken. Hollywood HDTV was the first online-movie provider in Thailand, which pioneered the market by providing Streaming focusing on the service of movie variety that included from the classic movies to the international movies. After that, Primetime was the second online-movie provider, which came to open the market in Thailand by highlighting the new movies and the swiftness of bringing the new movies into the online service. Next, it was Iflix, the famous movie provider from Indonesia, which concentrated the buffet online-movies, and another remarkable feature of Iflix was gathering the popular Western series to the utmost. For the main video streaming service provider with SVOD (Subscription Video on Demand), It was to provide watching online-TV by collecting monthly service fee, which the viewers could select to the movies to watch backwards. In Thailand, Netflix was the major provider as in many countries, which came to open the market by merging with many famous content creators of Thailand to produce and broadcast Thai series in some platforms such as Netflix, including Disney Plus, Mono Max, and Prime Video as well (NBTC, 2020). Providing the viewing movies through the Internet whether downloading or Streaming quite affected both the viewers and the service providers, together with the advance of the Internet technology, which was the key factor influencing the viewers to be able to access the movie sources easier because in the past, watching movies could be accessible in the movie theater platform only. Therefore, it caused the competition, and the movie industry businesspeople must adjust themselves in terms of the content to be watched. Hence, with all the factors mentioned, the researcher was interested in studying the strategy of creating the movie contents, which were different from the conventional watching movies in the movie theater. When digital technology came to redesign the watching movie platform of the viewers, it was prone to have other factors affecting the movie contents, which formerly were created to show in the movie theater only; however, presently it was the era of “Content is the King,” and based on Streaming, it was the opportunity and the extreme challenge for the content providers to create the attractive contents and make the profits for the movie businesspeople on the digital media.